MODELPlastics workshop - Modelling Ocean Plastic Litter in a Changing Climate: Gaps and future directions. (September 2019) - Martins, Irene; Bessa, Filipa; Gonçalves, Ana Marta M.; Gago, Jesús; Libralato, Simone
Abstract: Here we summarize the overarching issues that emerged from a workshop held to discuss scientific challenges and future directions on the use of numerical models to predict the amount, distribution and effects of plastic pollution on marine ecosystems. The need for multi-disciplinary approaches, standardized protocols for plastic quantification and analyses, using realistic contaminant concentrations in laboratorial experiments and targeting early-life stages of marine organisms were pointed out as needs to improve data accuracy. Participants also enumerated a list of gaps that include, identification of indicator organisms of plastic contamination, selection of biomarkers and the role of extreme events on plastic dynamics. Responding to these gaps will contribute to improve data quantity and quality and, thus, allow developing more reliable models. A crucial role is foreseen for modelling tools as they can incorporate the cumulative impacts of multiple stressors, including the individual-level effects of plastics, to the population- and ecosystem level. Highlights: Multi-disciplinary approaches are needed to tackle plastic pollution. Data quantity and quality must be improved to develop accurate models. Models are crucial tools to predict cumulative impacts of multiple stressors.